From stage to screen a theatre actor's guide to working on Camera - Britten, Bill (London Bloomsbury Publishing PLC, 2014)
"From Stage to Screen is a handbook for the professional actor packed with advice on how to make the transition and fully prepare for a TV or film role"-- Provided by publisher.
Let's pretend -- The big differences -- Showing and sharing -- The inner world -- Listening -- Commitment -- Filming : the big picture -- Understanding the shots -- Glossary of shots -- Hitting marks -- Overlap -- Continuity -- Positioning yourself for the camera -- The voice -- Facial awareness -- Playing the camera -- Loving the camera -- Getting the job -- Preparation -- Body heat : plot synopsis -- Preparing Teddy -- Preparing the text -- Mapping -- The readthrough -- At the hoot -- Who's who in the crew -- The process of shooting -- Rehearsal -- The take -- Additional dialogue recording (ADR) -- The finished product -- Professionalism.
Keywords: Motion picture acting